Intermittent Short Sleep Results in Lasting Sleep Wake Disturbances and Degeneration of Locus Coeruleus and Orexinergic Neurons - Zhu, Yan (Sleep, 2016)
STUDY OBJECTIVES: Intermittent short sleep (ISS) is pervasive among students and workers in modern societies, yet the lasting consequences of repeated short sleep on behavior and brain health are largely unexplored. Wake-activated neurons may be at increased risk of metabolic injury across sustained wakefulness. METHODS: To examine the effects of ISS on wake-activated neurons and wake behavior, wild-type mice were randomized to ISS (a repeated pattern of short sleep on 3 consecutive days followed by 4 days of recovery sleep for 4 weeks) or rested control conditions. Subsets of both groups were allowed a recovery period consisting of 4-week unperturbed activity in home cages with littermates. Mice were examined for immediate and delayed (following recovery) effects of ISS on wake neuron cell metabolics, cell counts, and sleep/wake patterns. RESULTS: ISS resulted in sustained disruption of sleep/wake activity, with increased wakefulness during the lights-on period and reduced wake bout duration and wake time during the lights-off period. Noradrenergic locus coeruleus (LC) and orexinergic neurons showed persistent alterations in morphology, and reductions in both neuronal stereological cell counts and fronto-cortical projections. Surviving wake-activated neurons evidenced persistent reductions in sirtuins 1 and 3 and increased lipofuscin. In contrast, ISS resulted in no lasting injury to the sleep-activated melanin concentrating hormone neurons. CONCLUSIONS: Collectively these findings demonstrate for the first time that ISS imparts significant lasting disturbances in sleep/wake activity, degeneration of wake-activated LC and orexinergic neurons, and lasting metabolic changes in remaining neurons most consistent with premature senescence. CITATION: Zhu Y, Fenik P, Zhan G, Somach R, Xin R, Veasey S. Intermittent short sleep results in lasting sleep wake disturbances and degeneration of locus coeruleus and orexinergic neurons. SLEEP 2016;39(8):1601–1611.